2021
DOI: 10.1186/s12889-020-10146-0
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and health status of 6,317 front line public health workers across five provinces in China during the COVID-19 epidemic: a cross-sectional study

Abstract: Background Public health workers at the Chinese Centre for Disease Control and Prevention (China CDC) and primary health care institutes (PHIs) were among the main workers who implemented prevention, control, and containment measures. However, their efforts and health status have not been well documented. We aimed to investigate the working conditions and health status of front line public health workers in China during the COVID-19 epidemic. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 30 publications
2
36
1
12
Order By: Relevance
“…The validated Chinese version of the Patient Health Questionnaire (PHQ-9) was used to assess the level of depression. Participants were asked to report how frequently they had experienced nine core depressive symptoms in the past 2 weeks ( 11 ). Items are assessed on 4-point Likert-type scales, ranged from not at all (0) to nearly every day (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validated Chinese version of the Patient Health Questionnaire (PHQ-9) was used to assess the level of depression. Participants were asked to report how frequently they had experienced nine core depressive symptoms in the past 2 weeks ( 11 ). Items are assessed on 4-point Likert-type scales, ranged from not at all (0) to nearly every day (3).…”
Section: Methodsmentioning
confidence: 99%
“…During the COVID-19 outbreak period, a recent survey conducted in the epicenter Wuhan, China found that approximately 30% of front-line medical workers reported severe anxiety compared to general medical staff in another city (16%), where the epidemic was not serious ( 10 ). Another survey of PHW across five provinces in China also reported a high prevalence of depression (21.3%) and anxiety (19.0%) ( 11 ).…”
Section: Introductionmentioning
confidence: 97%
“…The nature and extent of this impact across all sectors of public health, however, is not well understood. In a 2020 study of frontline workers focused and prevention and management of COVID-19 in China, one in five reported depression or anxiety, or both, and having worked through the night for at least 3 days in February–March 2020 [ 1 ]. A survey of workers in epidemiology and other areas of public health practice in the United States (U.S.) conducted in August–September 2020 found that two-thirds of respondents were experiencing burnout, with a greater prevalence among those who had been in their role for 1 to 4 years (as opposed to less than one), and those who worked in academia (as opposed to practice) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study found that the mental health problems of public health workers are also of concern, and further explored their specific sources of distress, such as: being treated differently at work, feeling aggrieved at work, family members not understanding and worrying about routine work outside the epidemic. Li et al found a higher reported rate of depression (21.3 %) and anxiety (19.0 %) among the public health workers in COVID-19 epidemic [ 9 ]. The mental health impact of the first wave of COVID-19 pandemic on Spanish healthcare workers were also reported with a prevalence of 28.1 % in major depressive Dissorder [ 10 ].…”
Section: Discussionmentioning
confidence: 99%